Implementasi Pelaksanaan Surat Edaran Mahkamah Agung RI Nomor 1 Tahun 2023 tentang Tata Cara Panggilan dan Pemberitahuan Melalui Surat Tercatat di Pengadilan Agama Majalengka Perspektif Fiqih Siyasah - Muhammad Iqbal; Efa Rodiah Nur; Fathul Mu’in (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the implementation of Supreme Court Circular Letter Number 1 of 2023 concerning Procedures for Summons and Notifications through Registered Mail at the Class IA Religious Court of Majalengka Regency, examined through Soerjono Soekanto's theory of legal effectiveness and the perspective of fiqh siyasah. This research employs an empirical juridical method with a qualitative approach, collecting data through interviews with judges, bailiffs, postal officers, and litigants, supported by literature studies. The findings indicate that the registered mail summons mechanism has been effectively implemented, consistent with the principles of a simple, fast, and low-cost judiciary. Despite technical obstacles in the retur procedure, this policy has demonstrably improved administrative efficiency and strengthened legal certainty for litigants. From the perspective of fiqh siyasah, the implementation of Circular Letter Number 1 of 2023 aligns with the principles of maslahah mursalah and siyasah qadha'iyyah in modern judicial administration.